URGENSI BAGIAN LAYANAN ANAK DAN REMAJA DI PUSAT PERPUSTAKAAN DAN PENYEBARAN TEKNOLOGI PERTANIAN - Sumanti, Dinda Ayu (Journal of Documentation and Information Science, 2017)
Indonesian Center for Agricultural Library and Technology Dissemination (ICALTD) as a special library of the government institutions under the Ministry of Agriculture has a vision, mission, duty, and special functions to support the activities of its mother-institutions. However, ICALTD has developed its organization by presenting library services for children and young-adult since 2013. The purposes of this research is to describe the conditions, activities, and programs on library services for children and young-adult. This research used qualitative approaches with descriptive methods. The results showed, although ICALTD has already taken a good inovation with its addition of services for children, the services has not been optimal. Some adjustments and policy should be make for the better services in the future.